Potensi inovasi Noken perempuan asli Baliem sebagai ekonomi kreatif dalam pengembangan pariwisata di kabupaten Jayawijaya: The innovation potential of Baliem women's Noken as a creative economy in tourism development In Jayawijaya Regency - Silooy, Telly Nancy; Misrah, Irmayani; Syarifah, Syarifah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
The purpose of this study was to identify and analyze the value and function of noken as local wisdom/culture of the Baliem Community; the role of noken as a creative economy for Baliem Indigenous Women and the opportunities for noken in tourism development. The research method is a qualitative method including ethnography, in-depth interviews, Focus Group Discussions (FGD) and case studies. The results of the study indicate that the value of noken in the life of the Baliem Community is a cultural symbol that cannot be separated from everyday life and is maintained from generation to generation. The philosophy of noken is a symbol of good life, love of peace, and fertility for the Community. Noken as a creative economy development is carried out through 1) empowering local communities to increase family income and have an impact on community welfare. 2). Innovation as a solution to survive in the face of competition in the development of the creative economy for the sustainability of the existence of noken in the future. 3). Noken has global marketing opportunities with high value 4). The sustainability of noken in the development of the Creative Economy requires the support of the Jayawijaya Regency government.